2018
DOI: 10.1016/j.jocn.2018.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Fatty infiltration of the cervical multifidus musculature and their clinical correlates in spondylotic myelopathy

Abstract: Cervical spondylotic myelopathy (CSM) is among the most common spinal cord disorders of the elderly. Muscle fat infiltration (MFI), a potential pathological sign of muscle adiposity, may contribute to or be associated with pain/disability/impairments in patients with CSM. We examined the relationship between MFI and CSM's clinical manifestations by enrolling nine CSM patients and five aged-matched controls to undergo MRI imaging of the cervical spine with MFI. A blinded investigator calculated MFI for each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 35 publications
4
48
0
Order By: Relevance
“…As such, the expression of MFI may embody one neurobiological basis underlying the transition to chronicity in a discrete, but not insignificant, number of these patients with persistent whiplash. It is noteworthy that the findings of MFI are not unique to whiplash injury, as similar MFI profiles have been observed, and reported, in DCM 1,2 , SCI 3 , but not idiopathic neck pain 8,30 , suggesting degenerative, and potentially traumatic, factors play a role in their development. More mechanistic work for understanding why and how MFI develops and its influence on recovery from trauma and other common degenerative processes is warranted and underway.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As such, the expression of MFI may embody one neurobiological basis underlying the transition to chronicity in a discrete, but not insignificant, number of these patients with persistent whiplash. It is noteworthy that the findings of MFI are not unique to whiplash injury, as similar MFI profiles have been observed, and reported, in DCM 1,2 , SCI 3 , but not idiopathic neck pain 8,30 , suggesting degenerative, and potentially traumatic, factors play a role in their development. More mechanistic work for understanding why and how MFI develops and its influence on recovery from trauma and other common degenerative processes is warranted and underway.…”
Section: Discussionsupporting
confidence: 80%
“…Muscle fat infiltration (MFI) has been described by conventional (T 1 - and T 2 -weighted) and advanced (Dixon and proton density fat fraction) magnetic resonance imaging (MRI) in cervical spine conditions, such as degenerative cervical myelopathy (DCM) 1,2 , spinal cord injury (SCI) 3,4 , and whiplash from a motor vehicle collision (MVC) 58 . While the mechanisms underlying these conditions greatly differ, the patterns of MFI appear consistent with the greatest magnitude occurring in the deepest, and most architecturally complex, muscular layer of the cervical extensors (i.e., multifidus and semispinalis cervicis) 57 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that fatty infiltration of paraspinal muscles was associated with spinal cord compression in degenerative cervical myelopathy. 20,23,24,29 Our results also indicated a significant correlation between the FI% of SCer at C5/6 and maximum occupancy ratio of OPLL in patients with cervical OPLL (Table 2), and the FI% of the paraspinal muscles was higher in the OPLL-CM group with a greater occupancy ratio of OPLL than in the OPLL-SL group. Muscle fatty infiltration is known to occur after skeletal muscle denervation, which is reportedly caused by spinal cord compression in cervical spondylotic myelopathy.…”
Section: Discussionsupporting
confidence: 71%
“…Several potential pathological mechanisms have been shown to contribute to functional disability in DCM, namely demyelination of spinal cord white matter regions/tracts [ 9 12 ], neuronal and volumetric loss of gray matter [ 13 ]. Fatty infiltration of cervical spinal musculature is emerging as a potential driver of disability [ 14 ]. An improved understanding of specific pathophysiological processes may inform both the clinical assessment of and management for patients with DCM.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle fat infiltration (MFI) is commonly observed in patients with cervical spine diseases including whiplash associated disorders (WAD) from a motor vehicle collision [ 15 ], traumatic spinal cord injury [ 16 ], and DCM [ 14 ]. Increased MFI in cervical flexors (longus capitis/colli and sternocleidomastoid muscles) [ 17 ] and extensors (multifidus and semispinalis cervicis) [ 18 , 19 ] is associated with increased pain and clinical disability in patients with WAD.…”
Section: Introductionmentioning
confidence: 99%